The Efficiency of Heavy Metal Analysis Method in Marine Fish Samples by Atomic Absorption Spectrophotometry - Jackson Siahaan; I Nyoman Loka; Jono Irawan; Mutiah Mutiah (Jurnal Penelitian Pendidikan IPA, 2022)
This research studies the efficient method for heavy metal analysis in marine fish samples by atomic absorption spectrophotometry. The dissolution of the samples used the wet destruction technique in 2 ways. The first method uses a mixture of HNO3, H2SO4, HClO4 (1:2:1), and the second method uses a mixture of HNO3and H2SO4 (1:1). Tuna (Euthynnus affinis) was taken as Marine fish samples. The results showed that the first method took 180 minutes with a % recovery of 98.79% - 99.55%. In contrast, the second method took 240 minutes and a % recovery of 98.08% - 98.45%. The results of measurements by atomic absorption spectrophotometry (AAS) using standard calibration curve and standard addition techniques are as follows: using standard regression curve technique obtained Pb (0.664 ± 0.067) mg/kg, Cu (2.780 ± 0.01) mg/kg, Cd (0.192 ± 0.044) mg/kg, and Zn (1.824 ± 0.075) mg/kg, while the standard addition method obtained Pb (0.612 ± 0.016) mg/kg, Cu (2.364 ± 0.016) mg/kg, Cd (0.148 ± 0.029) mg/kg and Zn (1.692 ± 0.016) mg/kg. The calculation of the level of accuracy of the analysis showed that the standard addition method RSD gave a precision value of 0.97% - 3.76% and the standard curve method RSD with a precision of 5.76% - 31.77%. In conclusion, (1) Heavy metal content in tuna (Euthynnus affinis) is still within the permissible limits. (2) wet digestion technique using a mixture of HNO3, H2SO4, HClO4 (1:2:1) can be more efficient. (3) The measurement results of the standard addition method give more precise results